Psychosis, psychedelic substance misuse and head injury: A case report and 23 year follow-up. (19th September 2015) - Sami, Musa; Piggott, Katie; Coysh, Claire; Fialho, Antonio
Abstract: Background : This study describes the case of a 57 year old gentleman with a previous severe brain injury who developed a severe psychotic disorder 19 years after the injury. This appears to have been precipitated by heavy psychedelic substance use, including cannabis, salvia divinorum, ketamine, LSD, cocaine and DMT amongst others. The psychosis remained in the absence of drug intoxication and was associated with prominent apathy, lack of concern and abulia. Case study : This study discusses the heavy psychedelic substance misuse possibly potentiating a transition to psychosis in this individual. Little work has been undertaken in this area as substance misuse has traditionally been an exclusion criteria for investigating psychosis in this patient group. Conclusions : It is suggested that psychedelic substance misuse should be investigated as a risk factor for psychotic illness in patients with brain injury, as this case clearly suggests.